2009
DOI: 10.1097/bsd.0b013e3181679bcb
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Spinal Injuries in Patients With Ankylosing Spondylitis or Diffuse Idiopathic Skeletal Hyperostosis

Abstract: Although the rate of neurologic injury was high for both groups, AS patients were more likely to exhibit neurologic deficits and undergo operative management. Although the majority of these spinal injuries were treated surgically, stable fractures without any associated neurologic deficits were often successfully managed with immobilization. Complications were observed with both operative and nonoperative treatments, although all of the deaths occurred in conjunction with the use of the halo-vest orthosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 16 publications
1
75
0
3
Order By: Relevance
“…Unfortunately, it has been shown that in a large percentage of cases, the correct diagnosis is not established until after the patient has already experienced a decline in neurologic function [17]. Unless there is a trauma with acute new back pain, spinal fracture in these patients may be easily overlooked.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, it has been shown that in a large percentage of cases, the correct diagnosis is not established until after the patient has already experienced a decline in neurologic function [17]. Unless there is a trauma with acute new back pain, spinal fracture in these patients may be easily overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…The initial radiograph of five patients with traumatic history was reported as without any bony injury in our series. The recognition of fractures and AL in individuals with AS may be complicated by their distorted bony anatomy and progressive deformity, making it more challenging to interpret radiographs [17]. Dilhman et al…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic compressive epidural hematoma is commonly reported in 23% of the patients with AS. 26 Significant ossification of the ligaments increased the risk of epidural hematoma, favored bleeding from the epidural venous plexus and the fractured bone. 32 Literature mentioned the possible co-existence of two 33 or multiple spinal fractures 34,35 in the advanced AS.…”
Section: Discussionmentioning
confidence: 99%
“…Enfin, selon Whang [16], une comparaison des fractures rachidiennes récentes liées à spondylarthrite et à la maladie hyperostosante de Forestier révèle que les troubles neurologiques sont plus graves sur les premières, sans constater de différence dans les traitements appliqués et les complications observées.…”
Section: Particularités Concernant Les Traumatismes Thoraco-lombairesunclassified